2014
DOI: 10.1158/1538-7445.am2014-3066
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3066: Establishment of a new method for the selection and detection of circulating tumor cells in metastatic breast cancer patients

Abstract: Background: Circulating tumor cells (CTCs) are discussed to be an ideal surrogate marker for individualized treatment options in metastatic breast cancer (MBC) since metastatic tissue may be difficult to obtain for repeated analysis. Here we established a new method for selection and detection of the heterogeneous CTC population using immunomagnetic enrichment followed by multi-marker profiling of genes related to different CTC phenotypes. Materials and Methods: Establishment of a nine gene qPCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Both kits employ immunomagnetic capturing of CTCs but different antigens are used, the EMT1 kit has antibodies against EpCAM and MUC1 whereas the EMT2 kit has antibodies against EpCAM, HER2, and EGFR. It has been suggested that the EMT2 kit can identify more mesenchymal CTCs that have passed through EMT [ 78 ]. The enriched CTCs were purified and lysed to retrieve mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Both kits employ immunomagnetic capturing of CTCs but different antigens are used, the EMT1 kit has antibodies against EpCAM and MUC1 whereas the EMT2 kit has antibodies against EpCAM, HER2, and EGFR. It has been suggested that the EMT2 kit can identify more mesenchymal CTCs that have passed through EMT [ 78 ]. The enriched CTCs were purified and lysed to retrieve mRNA.…”
Section: Methodsmentioning
confidence: 99%